Twelve tips for conducting educational design research in medical education. (1st September 2020) - Chen, Weichao; Reeves, Thomas C.
Abstract: Despite a steady growth in educational innovations and studies investigating the acceptance and effectiveness of these innovations, medical education has not realized sufficient improvement in practice and outcomes from these investments. In light of this lack of impact, there has been a growing call for studies that more effectively bridge the gap between research and practice. This paper introduces Educational Design Research (EDR) as a promising approach to address this challenge. Twelve tips are provided to inspire and guide medical educators to conduct EDR to achieve the dual goals of tackling a significant educational problem in a specific context while at the same time advancing the theoretical knowledge that may be used to improve practice elsewhere.